Word Formation Processes in the I-MATELAND K-pop Community Posts on X - Pratiwi, Ni Made Listya Ayu; Beratha, Ni Luh Sutjiati; Antari, Ni Made Suwari (DAS Institute, 2025)
New words are essential to a language since they help the speakers to express new concepts or ideas. These words can be created through word-formation processes. Words formed by word formation can be encountered everywhere, including in K-pop fan communities on social media. This study aims to identify the types and explain the process of word formation in the I-MATELAND community posts on X. The theory applied in this research is the theory of word formation by Yule. This research was conducted using a qualitative methodology. The data was collected using the documentation method, analyzed using the descriptive qualitative method, and presented using both formal and informal methods. This research revealed that the I-MATELAND community posts contained 70 K-pop jargons formed through word-formation processes. Nine out of the ten types of word formation processes were identified. These types were borrowing (11), compounding (11), blending (4), clipping (5), backformation (1), conversion (8), acronym (13), derivation (8), and multiple processes (9). By being found in 19% of the total data, the results showed that the acronym was the most common word formation process in the I-MATELAND community posts. However, coinage was not found in this study.